The role of conferences within Arctic governance. (2nd January 2021) - Steinveg, Beate
ABSTRACT: Since the end of the Cold War, the Arctic has transformed from a geopolitical buffer, to becoming a core national priority for the Arctic states, and a desirable playing field for non-Arctic actors. Geopolitical changes and a growing concern for the impacts of climate change have led to increased attention towards the Arctic region, which has prompted an extensive growth in the establishment of conferences attending to Arctic issues. Conferences are central meeting places for international and interdisciplinary cooperation, the exchange of ideas, and for deliberating the geopolitical structure of the Arctic. Yet, no systematic examination exists of the role conferences within the Arctic governance system. This article attends to the gap in the literature, by demonstrating how conferences supplement the work of the Arctic Council, regarding expanding the agenda, broadening stakeholder involvement, and improving communication and outreach.